Implementation of Advanced Coal-Biomass Blending and Fuel Stock Management at Pelabuhan Ratu Power Plant - Nurahman, Herowiko Thama; Hermawan, Heru (Department of Mechanical and Industrial Engineering, 2024)
The issue of climate change is of particular concern to countries around the world, including Indonesia. Many efforts are being and will be made to contribute to addressing climate change issues. Pelabuhan Ratu Power Plant (3 x 350 MW) belongs to PT PLN Indonesia Power. In line with the PLN Transformation (GREEN aspect) and the PT PLN Indonesia Power program (